Ring-Opening Metathesis of Benzene Induced by Rare-Earth Metallacycles - Liu, Wei; Zhang, Wen-Xiong (Synlett, 2025)
Activation of inert C–C bonds in arenes remains a formidable challenge in synthetic chemistry. Despite advances in arene C–C bond activation, metathesis transformations of aromatic C–C bonds remain largely unexplored. Recently, we uncovered a rare-earth metal-enabled intramolecular metathesis between a benzene C–C bond and a C–C single bond, assisted by the high reactivity and synergistic effect of rare-earth metallacycles. Mechanistic studies reveal a stepwise [2+2] cycloaddition/cycloreversion sequence via a fused tricyclic intermediate. This transformation expands the chemical space of arene reactivity, providing a rare example of aromatic ring-opening metathesis through a noncarbene pathway.
Keywords: Ring-opening metathesis; Rare-earth metals; Carbodianion; Metallacycle; Benzene